Forgive me, Leonard Peacock a novel - Quick, Matthew 1973- (Little, Brown and Company, 2013)
A day in the life of a suicidal teen boy saying good-bye to the four people who matter most to him
Keywords: Suicide; Suizid; Männliche Jugend; Jugendbuch